If it's not what You are looking for type in the equation solver your own equation and let us solve it.
t in (-oo:+oo)
-6*t = 42/11 // - 42/11
-6*t-(42/11) = 0
-6*t-42/11 = 0
-6*t-42/11 = 0 // + 42/11
-6*t = 42/11 // : -6
t = 42/11/(-6)
t = -7/11
t = -7/11
| -7w=35/9 | | 4k=-4 | | 1/6+m=1/4 | | 1+k=0 | | -3/4+k=13/4 | | 6/7+a=129/77 | | 5/6d=-5/18 | | 5/6a=-1/12 | | (3x+2)+2x=5 | | t+1/2=21/2 | | t+1=15/8 | | m-5/6=-5/12 | | a+5=0 | | 4+w=19/4 | | 2/5+k=2/5 | | -55/6=m-9 | | b-4=-47/10 | | d+1/3=10/3 | | w-5/7=-53/35 | | b-2/5=8/5 | | d+2/5=37/5 | | w-1/10=-1/10 | | -32/3=m+1/3 | | 4/3=n+1/3 | | 5/7+k=47/7 | | w+5=21/5 | | m-4/9=-1/63 | | m-1=-6/5 | | 2x=4/11 | | x-9=-57/7 | | b+8=44/5 | | m-8/9=91/9 |